Intrinsically microporous polymer-based hierarchical nanostructuring of electrodes via nonsolvent-induced phase separation for high-performance supercapacitors. Issue 19 (8th May 2018) - Jeon, Jun Woo; Han, Jae Hee; Kim, Sung-Kon; Kim, Dong-Gyun; Kim, Yong Seok; Suh, Dong Hack; Hong, Young Taik; Kim, Tae-Ho; Kim, Byoung Gak
Abstract : Hierarchically porous carbons derived from an intrinsically microporous polymer via a nonsolvent-induced phase separation show outstanding supercapacitor performance. Abstract : The growing demands of next-generation applications for high power and energy sources necessitate advances in hierarchically porous carbon-based energy storage materials, which improve the overall kinetics of electrolytic reactions by providing efficient ion and electron transport pathways and facilitate electrolyte infiltration into the electrode during charging/discharging. Herein, we fabricate hierarchically structured porous carbon electrodes (cNPIM), prepared by solution casting of a polymer of intrinsic microporosity (PIM-1) followed by nonsolvent-induced phase separation and carbonization. The obtained material exhibits a considerable surface area (∼2100 m 2 g −1 ), high electrical conductivity (150 S cm −1 ), high specific capacitances (345, 235, and 195 F g −1 in three-, two-electrode aqueous systems, and two-electrode organic systems, respectively) at 1 A g −1, and an exceptional specific energy of 43.2 W h kg −1 at a specific power of 1.25 kW kg −1, featuring a pore size gradient in the surface normal direction.